2020
DOI: 10.3390/molecules25061368
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Behaviour of Two Novel Azobenzene Fluorescent Dyes and Their Polymeric Blends

Abstract: Two novel symmetrical bis-azobenzene red dyes ending with electron-withdrawing or donor groups were synthesized. Both chromophores display good solubility, excellent chemical, and thermal stability. The two dyes are fluorescent in solution and in the solid-state. The spectroscopic properties of the neat crystalline solids were compared with those of doped blends of different amorphous matrixes. Blends of non-conductive and of emissive and conductive host polymers were formed to evaluate the potential of the az… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 63 publications
(39 reference statements)
0
12
0
Order By: Relevance
“…The excited state decay of the cis and trans isomers of azobenzenes in DMSO are generally in the ps timescale [34]. It was, however, found that bulky substituents close to the N=N linker or intramolecular hydrogen bonding slowed down the rotation around the nitrogen-carbon bond during photo-isomerisation, increasing the fluorescence performance of azobenzene compounds in solution [35]. In this study, both the free ligand and crystalline MOFs did not display fluorescent behaviour in solid-state; hence, the samples were suspended in DMF.…”
Section: Fluorescencementioning
confidence: 99%
“…The excited state decay of the cis and trans isomers of azobenzenes in DMSO are generally in the ps timescale [34]. It was, however, found that bulky substituents close to the N=N linker or intramolecular hydrogen bonding slowed down the rotation around the nitrogen-carbon bond during photo-isomerisation, increasing the fluorescence performance of azobenzene compounds in solution [35]. In this study, both the free ligand and crystalline MOFs did not display fluorescent behaviour in solid-state; hence, the samples were suspended in DMF.…”
Section: Fluorescencementioning
confidence: 99%
“…For a measurement of the angle-dependent polarized UV-vis absorption spectra at 320 nm, cast films were prepared by mixing a 5 wt% polymethyl methacrylate (PMMA) in DMF solution (PMMA: complex = 2:1). To evaluate the Weigert effect, we employed the R parameter to describe the degree of the photo-induced optical anisotropy [39][40][41][42]. Figure 7 exhibits the change of UV-vis spectra due to the transto cis-photoisomerization of azobenzene moiety of 1, which displays a shift of π-π* bands to a shorter wavelength [37].…”
Section: Spectral Characterization Of Complexesmentioning
confidence: 99%
“…For a measurement of the angle-dependent polarized UV-vis absorption spectra at 320 nm, cast films were prepared by mixing a 5 wt% polymethyl methacrylate (PMMA) in DMF solution (PMMA: complex = 2:1). To evaluate the Weigert effect, we employed the R parameter to describe the degree of the photo-induced optical anisotropy [39][40][41][42]. For a measurement of the angle-dependent polarized UV-vis absorption spectra at 320 nm, cast films were prepared by mixing a 5 wt% polymethyl methacrylate (PMMA) in DMF solution (PMMA: complex = 2:1).…”
Section: Spectral Characterization Of Complexesmentioning
confidence: 99%
“…The chromaticity values or CIE coordinates can be plotted on the CIE 1931 color space chromaticity diagram to provide a general overview of the varying colorimetric properties [37]. The values for step-wedge prints of cyan, magenta and yellow can be seen in Figure 7, for a weak ink set of 0.00108 wt%, 0.00176 wt% and 0.00176 wt%, respectively.…”
Section: Colour Tracking With Print Heightmentioning
confidence: 99%